INTERMEDIATE GRAMMAR STUDENTS’ MOTIVATIONS IN LEARNING ENGLISH - FBS, Listyani; Soegianto, Gifta Felicia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2020)
Abstract This study was intended to the grammar students and hopefully the lecturers might create new ways in teaching grammar. Since, many students failed the Intermediate Grammar Course and had to repeat the course. Open-ended questionnaires were used in the study which involved around 68% of the whole Intermediate Grammar students 2020. There were 46 out of 67 students who became the respondents of this study. Qualitative method was used in the study, and one student was interviewed. The study was conducted at the English Language Education Program (ELEP) of Faculty of Language and Arts (FLA), in a private university in Central Java, Indonesia. The participants were taken from students of Intermediate Grammar Course in Semester II, 2019-2020 aAcademic Year.. The results of the interview showed that Intermediate Grammar students had various motivations in learning English. The motivations which the students had were intrinsic, extrinsic, and instrumental motivations.